Indentation response of pressurized sandwich pipes filled with cement composite under lateral loading. (15th March 2021) - Wan, Feng; Guan, Feng; Deng, Yibo; Liu, Shaohu; Liu, Yonghui; Huang, Peng
Abstract: Sandwich pipe with cement composite core is capable of submarine pipelines application in deepwater harsh environment due to its superior structural resistance and energy absorption capacity. This work investigates the denting behavior of sandwich pipes under lateral quasi-static loading applied by the wedge-shaped denting tool, in the presence of internal content pressure and external hydrostatic pressure. The finite element models are established and validated against the available experimental results. Based on the finite element models, numerical simulations are carried out to investigate the load-indentation responses, stress states and failure modes of sandwich pipes along the loading histories. Furthermore, parametric studies are performed to examine the influence of internal and external pressure, tip radius, width and orientation of the wedge-shaped denting tool on the load-indentation response. Finally, an analytical model for load-indentation relationship prediction of thinner core sandwich pipes is developed. The comparison of analytical solutions and finite element results demonstrates a good agreement. Highlights: Lateral indentation response of pressurized sandwich pipes is investigated. Influence of pressures and denting tool related parameters on the denting resistance is evaluated. External pressure exhibits destabilizing effects on the denting resistance. A load-indentation relationship for sandwich pipes with a thinner core is derived.